An overview of historical development of the Khorchin story songs - Yingzhi, Zhang (Mongolian Journal of Arts and Culture, 2024)
The Khorchin, its unique cultural identity has been formed in the midst of various cultural diversity in which Donghu, Wuhuang, Xianbi, Kidan, Jurchen, Mongolian, Manchu, and Chinese people have been living one after and other. The uligert duu (tales in songs) has been enriched greatly its cultural content and meaning as it’s been connected to the social life, the mindset, traditional customs of local people. The purpose of research study is to outline the origin of the uligert duu, to clarify its historical stages, and to analyze the uligert duu versions found in oral and written sources as examples. The analysis method of research study is the main basis for this study, and it is carried out by summarizing the views of researchers and the overview of the subject. Хорчин үлгэрт дууны түүхэн хөгжлийн тойм Хураангуй: Хорчин нутагт дунху, ухуань, сяньби, кидан, жүрчэн, монгол, манж, хятад зэрэг үндэстэн ар араасаа оршин суусаар ирсэн бөгөөд төрөл бүрийн соёлын солилцооны дунд Хорчин нутгийн өвөрмөц соёл бүрэлдсэн байдаг. Хөгжлийн явцдаа үлгэрт дуу нь ард түмний нийгмийн амьдрал, сэтгэлгээ, ардын зан заншилтай уялдаж, илэрхийллийн хэлбэр, соёлын утга санааг улам баяжуулсаар байна. Бидний энэ удаагийн судалгааны зорилго хорчин үлгэрт дууны үүслийг тоймлон тодруулж, түүхэн хөгжлийн үе шатыг тодруулж, аман болон бичгийн сурвалжуудаас олж мэдсэн үлгэрт дууны хувилбаруудыг жишээ болгон шинжлэхийг эрхэм болгов. Тус судалгааг хийхэд судалгааны задлан шинжлэх арга гол суурь болох бөгөөд судлаачдын санаа бодол, эл сэдвийн хүрээний тойм судалгааг нэгтгэн дүгнэх аргаар гүйцэтгэсэн болно. Түлхүүр үгс: үе шат, хэв маяг, туульт дуу, уянгат шүлэг, морин эмээлийн дуу